Alternative mechanical heart valves for the developing world. (September 2020) - Wium, Elsmari; Jordaan, Christiaan Johannes; Botes, Lezelle; Smit, Francis Edwin
Due to the prevalence of rheumatic heart disease in the developing world, mechanical heart valves in the younger patient population remain the prostheses of choice if repair is not feasible. Despite their durability, mechanical valves are burdened by coagulation and thromboembolism. Modern design tools can be utilized during the design process of mechanical valves, which allow a more systematic design approach and more detailed analysis of the blood flow through and around valves. These tools include computer-aided design, manufacturing, and engineering, such as computational fluid dynamics and finite element analysis, modern manufacturing techniques such as additive manufacturing, and sophisticated in-vitro and in-vivo tests. Following this systematic approach, a poppet valve was redesigned and the results demonstrate the benefits of the method. More organized flow patterns and fewer complex fluid structures were observed. The alternative trileaflet valve design has also been identified as a potential solution and, if a similar design approach is adopted, it could lead to the development of an improved mechanical heart valve in the future. It is imperative that researchers in developing countries continue their search for a mechanical heart valve with a reduced thromboembolic risk, requiring less or no anticoagulation.